An Empirical Study on the Psychological Healing of Elderly Patients with Chronic Diseases by Combining Color Therapy with Art Creation - Mei, Peng (Pinnacle Academic Press Proceedings Series, 2026)
As the global population ages, the number of elderly patients living with chronic diseases is steadily increasing. In addition to long-term physical discomfort, these patients frequently experience psychological problems such as anxiety, depression, loneliness, and reduced self-worth, which can further aggravate their physical symptoms and form a vicious cycle. Traditional psychological interventions, while beneficial, often face limitations in accessibility, acceptability, and sustained engagement among older adults. Against this background, the present study investigates the psychological healing effects of combining color therapy with art creation for elderly patients with chronic diseases. Drawing on color psychology and art therapy theory, the study analyzes how specific color attributes and creative activities can influence emotional regulation, cognitive processing, and self-expression in this population. It further explores practical implementation methods, including guided color selection, structured and semi-structured art-making tasks, and supportive therapeutic settings tailored to the characteristics of elderly patients. The empirical findings confirm the feasibility and effectiveness of integrating color therapy with art creation as a complementary mental health intervention, demonstrating improvements in mood, emotional stability, and overall psychological well-being. This research provides an innovative approach to psychological care for elderly patients with chronic diseases and offers valuable theoretical and practical implications for enriching mental health service systems and enhancing quality of life in aging societies.